High-Security Multi-Level Joint Encryption Scheme Based on SCMA Chaotic Codebook and OCDM Subcarrier Disturbance - Zhongwen Ding; Bo Liu; Jianxin Ren; Zeqian Guo; Shuyu Zhou; Xiangyu Wu; Yaya Mao; Shuaidong Chen; Rahat Ullah; Yongfeng Wu; Zhipeng Qi (IEEE Photonics Journal, 2023)
Sparse code multiplexing access (SCMA) is a new code-domain non-orthogonal technique in the fifth generation mobile communication (5G), which can improve the quality of single-user link by orthogonal chirp-chirp division multiplexing (OCDM) modulation. In this paper, a SCMA-OCDM multi-core fiber transmission system based on chaotic system is proposed for next-generation passive optical networks (PON). The whole encryption process includes chaotic codebook design and frequency domain time domain block scrambling. A 49.42 Gb/s encrypted OCDM signal transmission experiment is carried out over 2 km of 7-core fiber, and the results show that the key space of the newly proposed encryption scheme can be up to 10251, and the reception sensitivity of OCDM is 1.7 dB higher than that of OFDM when the BER is 3.8 × 10−3. In addition, the performance of the orthogonal hexagonal chaotic codebook transmission system is 2.5 dB better than that of traditional codebooks. This scheme can improve the security of encrypted information and system performance, and has a broad application prospect in future optical access networks.